2022
DOI: 10.1002/chem.202200286
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Frustrated Aromatic Enes with Various Colors Originating from Multiple Folded and Twisted Conformations in Crystal Polymorphs**

Abstract: Overcrowded ethylenes composed of 10‐methyleneanthrone and two bulky aromatic rings contain a twisted carbon–carbon double (C=C) bond as well as a folded anthrone unit. As such, they are unique frustrated aromatic enes (FAEs). Various colored crystals of these FAEs, obtained in different solvents, correspond to multiple metastable conformations of the FAEs with various twist and fold angles of the C=C bond, as well as various dihedral angles of attached aryl units with respect to the C=C bond. The relationship… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…In nature, double-bond isomerization forms the functional basis of the retinoid cycle responsible for human vision 6 , with fine-tuning provided by molecular distortions of the chromophore 7 . In the laboratory, twistable double bonds have been incorporated into molecular switches and motors 5 , switchable chromophores 2 , 8 10 and organic magnetic materials 11 17 . The performance of such molecular devices critically depends on the electronic and steric features of the π system containing the switchable bond.…”
Section: Mainmentioning
confidence: 99%
“…In nature, double-bond isomerization forms the functional basis of the retinoid cycle responsible for human vision 6 , with fine-tuning provided by molecular distortions of the chromophore 7 . In the laboratory, twistable double bonds have been incorporated into molecular switches and motors 5 , switchable chromophores 2 , 8 10 and organic magnetic materials 11 17 . The performance of such molecular devices critically depends on the electronic and steric features of the π system containing the switchable bond.…”
Section: Mainmentioning
confidence: 99%
“…The geometries other than the folded and twisted forms are frozen in crystal lattices and can be analyzed by X-ray . The study of 14 demonstrates that highly congested and hindered OCEs and quinodimethanes can adopt a variety of geometries in the crystal lattice when the energy difference is small enough to be compensated by the packing force …”
Section: Difference Between the Open-shell Perpendicular Form And The...mentioning
confidence: 99%
“…Upon applying the pressure, the color of single crystal 1 gradually changed from red (0 GPa) to dark red (5.0 GPa), that is, piezochromic behavior even though 1 has no flexible π-skeletons which readily reflect the structural change by its color. [30][31][32] (Figure 12A), X-ray crystallography under high pressure revealed that the C-C distances of C9-C9 0 and C10-C10 0 are slightly shortened from 2.777 Å to 2.755 Å and 2.826 Å to 2.788 Å, respectively (Figure 12B). TD-DFT calculations of 1 showed that the longer-wavelength shift of the HOMO-LUMO transition by applying pressure from 543 nm (f = 0.0017) to 592 nm (f = 0.0029) was observed (Figure S18).…”
Section: Attempt To Enhance the Antiaromaticity Of 1 Using Hydrostati...mentioning
confidence: 99%